2013
DOI: 10.1590/s1516-35982013001000001
|View full text |Cite
|
Sign up to set email alerts
|

Intake, performance and nutrient digestibility of sheep fed sugarcane treated and ensiled with calcium oxide or urea

Abstract: -The objective of this study was to evaluate intake, performance and nutrient digestibility of sheep supplemented with sugarcane ensiled with four levels of calcium oxide (0.0, 0.8, 1.6 and 2.4%) and urea (1.5%), on a natural matter basis. Twenty castrated Santa Ines lambs with 24.09 kg average weight were housed in individual 1.5 m 2 pens, distributed in a completely randomized design. The diet supplied had a roughage:concentrate ratio of 70:30 and the experimental period lasted 77 days, of which 14 days were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The reduction of protein contents with the addition of CaO is thought to result in dilution of CP because this component is absent from the additive in question, which adds to the loss of nitrogen compounds during volatilization. This assumption was confirmed by Magalhães et al (2013), who evaluated the chemical composition and fermentation loss of sugarcane silages with different Brix degrees, both with and without CaO. In this study, the increase in Brix in the sugarcane decreased linearly with the CP content of the material that was ensiled, which shows that as the material matures, there is a reduction in its dietary value that results from the increases in the constituents of the cell wall and total sugars.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The reduction of protein contents with the addition of CaO is thought to result in dilution of CP because this component is absent from the additive in question, which adds to the loss of nitrogen compounds during volatilization. This assumption was confirmed by Magalhães et al (2013), who evaluated the chemical composition and fermentation loss of sugarcane silages with different Brix degrees, both with and without CaO. In this study, the increase in Brix in the sugarcane decreased linearly with the CP content of the material that was ensiled, which shows that as the material matures, there is a reduction in its dietary value that results from the increases in the constituents of the cell wall and total sugars.…”
Section: Discussionsupporting
confidence: 59%
“…The addition of alkaline additives to the cell wall of the fodder solubilizes the fibrous components, as stated in the study of Brienzo et al (2016). The implication is that alkaline environment helped to increase the digestibility of sugarcane, possibly by reducing ADF and LIG, which corroborates findings of Magalhães et al (2013). Huang et al (2016) evaluated the effect of additives in the treatment of sugarcane bagasse (SCB) and reported that the C 2 H 5 ONa pre-treatment showed the best effect on hydrolysis of SCB.…”
Section: Discussionmentioning
confidence: 56%